Pengembangan Sistem Informasi Perjalanan Dinas Menggunakan Kerangka Kerja Scrum - Fredrikus Suarezsaga; Daniel Nugraha; Alfred Yulius Arthadi Putra (Institut Teknologi Garut, 2022)
Official travel is an activity carried out by every government agency. Official travel has two types of documents, namely the Assignment Order document (SPT) and the Official Travel Letter (SPD). Another document is the report on the results of the implementation of official travel to the official signing the SPT. Administrative management of official travel is done manually using work applications such as MS Office. This is very susceptible to writing errors, SPD manipulation, discrepancies in outgoing money and the number of business trips made, and discrepancies in financial reports. An official travel information system was developed to handle this. This research consists of 3 stages, the first is the data collection stage consisting of observation and interviews, the second stage is determining development needs, and the third is the development of an official travel information system using the Scrum framework methodology. The Scrum framework consists of determining Product Backlog Items, Sprint Planning, Daily Scrum, and Sprint Review. Product backlog items are determined as many as 9 items, with details of a total of 34 tasks carried out. The total estimated days set in working on 9 items is 36 days with a development team of 3 people. The sprint is divided into three parts, where in the first sprint do 4 items, 12 tasks, done for 13 days. The second sprint does 2 items, 12 tasks, done over 11 days. The third sprint does 3 items, 9 tasks, done over 10 days. Each sprint generates a burndown chart that shows a graph of completed tasks. Each sprint is completed according to the estimated number of days. The results of the sprint are then presented in a sprint review which produces the design and functionality of the features defined in the product backlog items. The Scrum framework can be used as a method in developing business travel information systems that can complete 9 features within 36 days, divided into 3 sprint stages.